Application of Kumon Learning Model to Improve Student Learning Outcomes in Economic Math Subject - Nur Fajri; Asmaidi Asmaidi (Jurnal Inotera, 2020)
This research aims to study the effectiveness of Kumon learning model against the increasing of student grade at Economic Math subject at STIMI Meulaboh. Quasi experiment method with pretest-posttest is used. The population used by model is students of Management Economic at STIMI Meulaboh that follow Economic Math subject at odd semester of the 2018/2019 school year. The students at Room 1 consist of 30 students are chosen as sample. The test instrument is used to collect the data for research. The research implementation procedure provides pretest in the beginning of the meeting and compares the result with posttest after Kumon learning model is applied on all samples. The result of pretest and posttest are used as research data. The research result point out that Kumon Learning Model helps students to increase their grade at Economic Math subject at STIMI Meulaboh..